Analisis Sistem Pengendalian Internal Atas Pembayaran Dana Pensiun Pada PT XYZ (Persero) Cabang Yogyakarta - Vika Aleyda Zahra; Maulidyati Aisyah (Jurnal Rimba Riset Ilmu manajemen Bisnis dan Akuntansi, 2024)
This study explores the implementation of internal controls over pension fund payments at PT XYZ (Persero) Branch Yogyakarta using the COSO (Committee of Sponsoring Organizations of the Treadway Commission) 2013 framework. Effective accounting systems are considered crucial in supporting company activities, including pension fund management. Cash disbursement systems are the primary focus in managing company operations, with the aim of improving effectiveness and preventing fraud. Previous studies indicate the necessity of internal controls to detect and prevent fraud, with COSO being a relevant framework in this regard. Qualitative analysis method was employed in this study, with primary data collected through interviews and documentation. The results indicate that PT XYZ (Persero) Branch Yogyakarta has effectively implemented internal controls, in line with the principles outlined in the COSO 2013 framework.